Carpal Tunnel Syndrome: A Literature Review - Oliveira, Jaime (Gazeta Médica, 2021)
Carpal tunnel syndrome (CTS) affects 3% of the population and is due to compression of median nerve in the carpal tunnel. This article aims to review the scientific evidence about CTS. A narrative review was carried out. One hundred and sixty one articles were identified in the research and data referring to 26 bibliographic references were included in the review. CTS affects women more. The diagnosis is clinical. Classical symptoms are pain, dysesthesias and/or paresthesias in the palmar region, from the thumb to the radial surface of annular. When positive, provocative manoeuvres increase diagnostic suspicion. Electrodiagnostic tests are important for diagnostic confirmation, severity stratification and treatment definition. If the disease is mild/moderate, conservative treatment is initially recommended. In moderate/severe cases, surgery is recommended. CTS is disabling. When there are symptoms, this diagnosis must be considered and provocative tests performed. Electrodiagnostic tests are important for diagnosis and definition of therapy.